Use of concentric linear velocity to monitor flywheel exercise load - Martín-Rivera, Fernando; Beato, Marco; Alepuz-Moner, Vicente; Maroto-Izquierdo, Sergio (Frontiers in Physiology, 2022)
Purpose: To propose the concentric linear velocity measurement as a valid method to quantify load and individualise the prescription of flywheel training, we investigated the relationship between inertial load and mean concentric linear velocity (MCLV) during the flywheel squat exercise in a wide spectrum of intensities. In addition, we compared MCLV and subjective rating of perceived exertion (RPE) after each load. Methods: Twenty-five physically active men volunteered for this study (26.5±2.9 years, 179.5±4.2 cm, 81.6±8.6 kg). After familiarization, all participants performed two inertial progressive load tests on separated days to determine the flywheel load-velocity profile and its reliability. Each participant performed 5 set of 6 repetitions of the flywheel squat exercise with different inertial loads (0.047, 0.104, 0.161, 0.245, 0.321 kg·m2) selected in a counterbalanced and randomized order for each testing day. Average MCLV and RPE for each load were compared. Results: The inter-session intraclass correlation coefficient (ICC) showed values above 0.9 in all the included outcomes (MCLV: ICC=0.91; RPE: ICC=0.93). A significant correlation (p<0.01, R2=0.80) between inertial load and MCLV was found. Similarly, significant correlation models (p<0.01) were observed between RPE and load (R2=0.87) and (R2=0.71) between RPE and MCLV. Conclusion: The control of MCLV during flywheel exercise can be proposed as a valid method to quantify load and to individualize the prescription of flywheel training. In addition, RPE responses have demonstrated significant correlations with load and velocity. Therefore, RPE has been proposed as a valid and reliable alternative to control flywheel training.